Metabolic effects of early protein undernourishment and renourishment in wistar rats (Bioscience Journal, 2015)
Malnutrition remains a important public health condition by affecting mostly children. The present study aimed to examine the effects of prenatal protein undernourishment and postnatal renourishment on the metabolism of pre-adult animals. Forty-five male Wistar rats originating from different litters were used. The Nourished (N, n=15) and Undernourished (U, n=30) groups were maintained on proteic and hypoproteic diets (20% and 5% casein, respectively) from the intrauterine phase until the end of the experiment. The Renourished group (R) contained 15 animals, randomly chosen from U group, that consumed the N diet beginning on day 21 (weaning). All groups were maintained until day 60. The experimental data was acquired daily for body weight, feed and water intake, feces and urine excretion. Data analysis was made with the total results and the ratio between them. The U group animals developed uniformly sparse hair late and experienced intense sweating, features that were not observed during the experiment in the R and N animals groups. The R group had the largest weight gain and feed and water intake ratio/weight at experimental period, followed by the N group animals. The final body weight and food intake decreased gradually in the order N-R-U, but none of the other parameters showed a statistical difference between the N and R animals. Compared to groups N and R, the U group animals consumed 90% and 81% more food and water, respectively. Protein undernourishment induced metabolic dysfunction in the U group animals. The similarity in the experimental parameters of the N and R groups suggests that an early feeding correction was effective in reestablishing the organic functions of the R group animals.